2020
DOI: 10.20517/2574-1225.2020.09
|View full text |Cite
|
Sign up to set email alerts
|

Current management of gastroesophageal reflux disease in the obese population - a review of the literature

Abstract: The current obesity pandemic has a clear impact on quality of life and health resource utilization; hence it has become a significant global health concern. Multiple obesity-related comorbidities such as gastroesophageal reflux disease (GERD) are frequently observed among this patient population. GERD is a complex disease with multiple elements contributing to the failure of the anti-reflux barrier. If left untreated, the excessive reflux of gastric contents into the esophagus can give rise to multiple complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…This echoes the results published from a retrospective review of the Bariatric Outcomes Longitudinal Database between 2007 and 2010 that demonstrated LVSG was associated with persistent symptoms in the majority (84.1%) of patients experiencing GERD preoperatively, with a greater likelihood of postoperative complications including the need for revisional surgery 28. These further confirm the recommendations that the presence and/or severity of GERD needs to be considered in the selection of procedure for optimal bariatric surgical outcomes, and in severe cases may be considered as a relative contraindication to LVSG 29–31…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This echoes the results published from a retrospective review of the Bariatric Outcomes Longitudinal Database between 2007 and 2010 that demonstrated LVSG was associated with persistent symptoms in the majority (84.1%) of patients experiencing GERD preoperatively, with a greater likelihood of postoperative complications including the need for revisional surgery 28. These further confirm the recommendations that the presence and/or severity of GERD needs to be considered in the selection of procedure for optimal bariatric surgical outcomes, and in severe cases may be considered as a relative contraindication to LVSG 29–31…”
Section: Discussionsupporting
confidence: 76%
“…28 These further confirm the recommendations that the presence and/or severity of GERD needs to be considered in the selection of procedure for optimal bariatric surgical outcomes, and in severe cases may be considered as a relative contraindication to LVSG. [29][30][31] Amongst patients receiving LRYGB, on the other hand, surgical repair of internal hernias was the primary reason necessitating surgical reintervention. Internal hernias are a well-recognized complication associated with LRYGB and are reported to occur in up to 14% of patients receiving this surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Moreover, Barrett’s esophagus, esophageal stricture, and esophageal adenocarcinoma are the serious complications associated with GERD. 6 …”
Section: Introductionmentioning
confidence: 99%
“…1 Gastroesophageal reflux disease (GERD) is one of the most commonly obesity-associated comorbidities, with an incidence of 22% to 70% in patients with obesity. 2 The increasing incidence of obesity is expected to cause a simultaneous increase in the prevalence of GERD. Furthermore, obesity has been shown to be a significant risk factor for GERD sequelae, including erosive esophagitis, and Barrett's esophagus, with a risk of progression to esophageal adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%